Raising Students’ Awareness on Word Stress in Teaching Listening - Wulan Fauzanna (Universitas Negeri Padang, 2014)
Listening skill for English as Foreign Language learners is important to make the communication understood among the speakers and avoid misunderstanding. In teaching listening, teacher points that students find the difficulties to understand the words they hear because of lack of exposure to English words sounds and not familiar with the words sound (Cohen, 2007). To deal with this problem, teacher should starts to expose students to the new words in the intensive listening practice. Students learn to listen closely to the sounds, words and phrases. In this activity, teacher can introduce new vocabulary which is available in the text before the listening activity. In this activity, teacher raises student’s awareness on word stress. Word stress is when we pronounce a word based on the number of syllable which receives stress. The sound it produces can make rhythm which makes students familiar with the word. Students can practice pronounce words; content words and function words before each listening activity. In pre-listening activity, word stress is introduced, students will be more aware of the words they will hear during listening process. The study emphasizes that integrating word stress in teaching listening can help students improve their listening ability and achieve comprehension.